CONSUMER AND INNOVATIONS IN E-HEALTH SERVICES examples of european countries. - Dąbrowska, Anna (Economist) (PRODUCTIVITY PRESS, 2025)
Innovations in e-health can significantly enhance healthcare accessibility, efficiency and patient safety. The advancements, such as telemedicine and electronic health records, facilitate remote access to healthcare services, reducing geographical barriers and addressing the urgent needs of patients. Moreover, they enable healthcare providers to deliver more personalized and accurate healthcare services thanks to integrating technologies like artificial intelligence. Ehealth optimizes healthcare costs, addresses current, pressing needs of individuals, communities and societies and adapts to the changing landscape of healthcare, making it a crucial and highly relevant topic in todays world. This book discusses critical aspects associated with the implementation of technological innovations in the e-health market. The authors have identified the technological innovations introduced in the e-health sector during the last decade of the twenty- first century and explored how patients are adapting to and managing these technological advancements. The authors conducted research in four selected European countries: Poland, Finland, Estonia and Spain, with a focus on understanding the extent to which these new technological solutions have been embraced by demand- side actors, that is, recipients/users of e-health services. The resulting book aims to address the following questions: What barriers do new technological solutions encounter in their implementation? Do the e-health services and solutions contribute to improving health and extending life expectancy in individual European countries? The book offers a comprehensive overview of innovations in digital health services, concentrating on this sector as evaluated by the institutions responsible for their functioning and the development of the supply side of e-health services. Additionally, the book provides an in- depth analysis of patients attitudes toward technological advancements in medical services, focusing on their interaction with digital healthcare solutions and assessing the willingness of e-patients to incorporate cutting-edge e-health services into their health- related behaviors. Finally, the book presents an analysis and assessment of using technological solutions to enhance the efficiency and effectiveness of the healthcare system in Europe. It provides practical insights and a comprehensive view of innovations and e-services in healthcare, catering to a diverse audience, including practitioners and managers of healthcare entities, patients, tech start- ups, researchers and students.
Keywords: Medical telematics.; elektronické knihy; electronic books